Intercalation pseudocapacitance of expanded graphite in sodium‐ion capacitors. (1st May 2018) - Zhang, Zhendong; Zhao, Jiachang; Guo, Chaofei; Xu, Jingli
Abstract : The intercalation pseudocapacitance of expanded graphite (EG) which was prepared by a process of oxidation and partial reduction on pristine graphite was investigated in this work. The structure of EG was characterised by X‐ray diffraction (XRD) and high‐resolution transmission electron microscope (HRTEM), and the electrochemical performance of EG was measured by cyclic voltammetry, galvanostatic charge–discharge and electrochemical impedance spectroscopy. The interlayer distance of EG is enlarged from 0.34 to 0.40 nm, which is demonstrated by XRD and HRTEM. EG electrode exhibits a specific capacitance of 228 F/g at current density of 0.5 A/g. Moreover, the material shows excellent cycle stability after 2000 charge–discharge cycles at a current density of 1 A/g. EG could be a very promising material for the supercapacitors industry.